WAYS TO FORM THE READINESS OF CHILDREN OF PRIMARY SCHOOL AGE WITH UNDERDEVELOPED SPEECH FOR WRITTEN SPEECH - Maxmudov Xurshid Shuxratovich; Ergasheva Saidaxon Qobuljon qizi; Muminova Mubinaxon Mirzajon qizi (Bright Mind Publishing, 2025)
Through the article, you can get information about recommendations for forming the readiness of children of primary school age with underdeveloped speech for written speech, the system and directions of work aimed at creating the functional basis of written speech, and technologies that allow for the prevention of written speech defects, as well as the rapid and effective mastery of written speech.
Keywords: Writing, speech, visual activity, phonemic perception, literacy training period, oral speech, phonemic perception, cognitive processes, abilities.